Morphology control of encapsulated gold nanoparticles. - Wang, Xinjiao. (2008)
This thesis contains two different parts: organometallic chemistry and nanoscience since it was completed in two different groups. In the first part of this thesis, an iridium N-heterocyclic carbene complex with a rare hydrogen wingtip was obtained via C-N bond cleavage. The C-bound to N-bound tautomerization of this carbene can not be achieved in this neutral 18-electron Ir(III) complex. Chloride abstraction in MeCN afforded an NHC-acetimidamide complex, where the N-bound to C-bound tautomerization of this carbene was observed in CDCl3 at 110 oC. Crystal structures of iridium complexes with these rare ligands were reported. In the second part, gold nanoparticles coated with amphiphilic block copolymer (PS-PAA) were found to aggregate in DMF/H2O mixture solutions with well-behaved second-order kinetics. The resulting aggregates were characterized by TEM and UV-vis spectroscopy. With repeated centrifugation, we were able to isolate and enrich the population of dimers and trimers from the reaction mixture. In another project, we prepared different morphologies of asymmetric encapsulated AuNPs. The asymmetrically encapsulated gold nanoparticles (a-[AuNP@polymer]) were prepared in high yield, high throughput and high monodispersity. The formation of a-[AuNP@polymer] was studied at different temperature, solvent quality, reaction time and reactant concentrations and characterized by TEM.